Orthopedics and Trauma in Children - Horsch, Axel A.; Ghandour, Maher A.; Klotz, Matthias Christoph M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Discover the complexities of pediatric orthopedics in this comprehensive reprint book. Pediatric orthopedics present unique challenges in diagnosis and treatment, necessitating the expertise of skilled specialists. Congenital, developmental, and acquired orthopedic issues, including infectious, neuromuscular, nutritional, neoplastic, psychogenic, and traumatic conditions, are explored. With a focus on evidence-based recommendations, this book addresses the management of orthopedic deformities in children by considering different clinical scenarios. From upper and lower limb injuries to severe trauma, readers will gain insights into decision-making processes for reconstruction or amputation. As a valuable resource for orthopedic surgeons, pediatricians, and healthcare professionals, this reprint fills knowledge gaps to optimize patient care.